2014
DOI: 10.1177/0022034514536730
|View full text |Cite
|
Sign up to set email alerts
|

Selective β2-adrenergic Antagonist Butoxamine Reduces Orthodontic Tooth Movement

Abstract: Recently, involvement of the sympathetic nervous system in bone metabolism has attracted attention. β2-Adrenergic receptor (β2-AR) is presented on osteoblastic and osteoclastic cells. We previously demonstrated that β-AR blockers at low dose improve osteoporosis with hyperactivity of the sympathetic nervous system via β2-AR blocking, while they may have a somewhat inhibitory effect on osteoblastic activity at high doses. In this study, the effects of butoxamine (BUT), a specific β2-AR antagonist, on tooth move… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…Adrb1/2 -/-mice showed a decrease in osteoclast differentiation and OTM distance. Although OTM distance may also be affected by other SNS-regulated activities, such as masticatory movement and alveolar bone density (Passatore and Roatta, 2007;Sato et al, 2014), our data provide a novel mechanism by which SNS-regulated OTM is mediated by force-induced Adrb2 activation. In previous studies, animal models were used to investigate the function of SNS in bone mechanoadaptive responses, such as tail suspension and sciatic neurectomy.…”
Section: Discussionmentioning
confidence: 85%
“…Adrb1/2 -/-mice showed a decrease in osteoclast differentiation and OTM distance. Although OTM distance may also be affected by other SNS-regulated activities, such as masticatory movement and alveolar bone density (Passatore and Roatta, 2007;Sato et al, 2014), our data provide a novel mechanism by which SNS-regulated OTM is mediated by force-induced Adrb2 activation. In previous studies, animal models were used to investigate the function of SNS in bone mechanoadaptive responses, such as tail suspension and sciatic neurectomy.…”
Section: Discussionmentioning
confidence: 85%
“…The sympathetic nervous system regulates bone metabolism by decreasing osteoblast activity and increasing osteoclast activity (Elefteriou et al, ; Togari & Arai, ; Takeda et al, ). Tooth movement is increased by increased bone metabolic turnover due to sympathetic activation (Kondo, Kondo, Miyazawa, Goto, & Togari, ; Sato et al, ). A previous study reported that spontaneously hypertensive rats (SHR) with sympathicotonia (Klemola, Huttunen, Laine, Weckström, & Hirvonen, ; Nagatsu et al, ; Wang, Hsu, Jee, & Matthews, ) have hypertension and osteoporosis due to decreased lumbar and tibial bone mass (Sato, Arai, Goto, & Togari, ).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that spontaneously hypertensive rats (SHR) with sympathicotonia (Klemola, Huttunen, Laine, Weckström, & Hirvonen, ; Nagatsu et al, ; Wang, Hsu, Jee, & Matthews, ) have hypertension and osteoporosis due to decreased lumbar and tibial bone mass (Sato, Arai, Goto, & Togari, ). It was recently reported that SHR with sympathicotonia result in increased tooth movement distance and decreased alveolar bone mass and that the selective β2‐adrenergic receptor (β2‐AR) blocker butoxamine decreases tooth movement and restores decreased maxillary alveolar bone volume (Sato et al, ). In the absence of tooth movement, alveolar bone formation did not differ between SHR and WKY, and bone resorption tended to be high, but alveolar bone mass did not change (Sato et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, application of mediators such as human growth hormone, nitric oxide, osteocalcin, parathyroid hormone, prostaglandins, and vitamin D has all shown to increase OTM . Conversely, in addition to OPG, bisphosphonates, butoxamine, echistatin, estradiol, MMP inhibitor, nitric oxide synthase inhibitor, and prostaglandin inhibitors contribute to decreased tooth movement . Further experiments are required to determine the optimal dosage and frequency, the efficiency of gene vs protein delivery, the determination of any systemic side effects, and the costs associated with such interventions prior to the utilization of biologic/pharmacologic agents as a part of standard orthodontic therapy.…”
Section: Precision Biomedicine In Orthodonticsmentioning
confidence: 99%